Compliance capitalism : how free markets have led to unfree, overregulated workers - Dekker, Sidney (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"In this book, Sidney Dekker sets out to identify the market mechanisms that explain how less government paradoxically leads to greater compliance burdens. This book gives shape and substance to a suspicion that has become widespread among workers in almost every industry: we have to follow more rules than ever-and still, things can go spectacularly wrong. Much has indeed been privatized and deregulated, giving us what is sometimes known as 'new public management,' driven by neoliberal, market-favoring policies. But, paradoxically, we typically have more rules today, not fewer. It's not the government: it's us. This book is the first of a three-part series on the effects of 'neoliberalism,' which promotes the role of the private sector in the economy. Compliance Capitalism examines what aspects of the compliance economy, what mechanisms of bureaucratization, are directly linked to us having given free markets a greater reign over our political economy. The book steps through them, picking up the evidence and levers for change along the way. Dekker's work has always challenged readers to embrace more humane, empowering ways to think about work and its quality and safety. In Compliance Capitalism, Dekker extends his reach once again, writing for all managers, board members, organization leaders, consultants, practitioners, researchers, lecturers, students and investigators curious to understand the genuine nature of organizational and safety performance"--
The freedom to make more rules -- Free markets in theory; intensive managerial control in practice -- The Macro: Sell out and pull out -- The Meso: Mistrust and monitor -- The Micro: Audit and cash in -- How governments missed this -- A retreat into rules.
OCLC-licensed vendor bibliographic record.
Keywords: Deregulation; Free enterprise; Industries -- Self-regulation.; Employee rules; Labor; Bureaucracy; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Quality Control